PIDANA MATI DALAM PERSPEKTIF PERADILAN DI INDONESIA - Muzakkir, Faisal A. Rani, Dahlan Ali. (Jurnal Ilmu Hukum, 2014)
Abstract: The death penalty is a punishment that is imposed by a court or no court , gross misconduct or serious criminal offenses and the death penalty is a component that is related , it is still found to overlap the interpretation and implementation of the judicial power of authority between the Constitutional Court and the Supreme Court against a provision of law legislation , particularly with regard to capital punishment , and the judiciary has yet to implement fully implement the provisions of the legislation containing the threat of the death penalty and the execution of death row inmate still lead to discrimination and problems , so that it raises issues and legal uncertainty. Research shows that, in the perspective of the Constitutional Court against the death penalty principle that capital punishment is not contrary to the Constitution of the Republic of Indonesia Year 1945 . While the Supreme Court in a ruling decided that the death penalty is contrary to the Human Rights and the Constitution of the Republic of Indonesia Year 1945 , but there are also other decision affirming the death penalty , so the Supreme Court looks inconsistent . The application of the provisions of the legislation that contains a sentence of death for every criminal there is still discrimination, particularly the imposition of the death penalty is still limited to the crime of murder and terrorism . Process execution on death row there is still a problem , namely the existence of discrimination against the execution of the convict . Konstistusi Court and the Supreme Court as a judicial institution and other relevant state institutions , in every decision and future changes in the Penal Code , relating to the death penalty should be maintained and be consistent . Of the offenses punishable by death , and certain other criminal offenses judiciary is advisable to carry out fully and be objective . As well as the execution process , either period or the rights of death row inmates and the concrete rules should be formulated in a verdict dikontruksikan , so the legal certainty of the execution process , and the rights of death row inmates. Keywords:The Death Penalthy, Justice, Inodesia. Abstrak: Pidana mati adalah hukuman yang dijatuhkan pengadilan terhadap kejahatan berat atau tindak pidana serius. Saat ini masih ditemukan tumpah tindih penafsiran dan pelaksanaan kewenangan kekuasaan kehakiman antara Mahkamah Konstitusi dengan Mahkamah Agung terhadap sebuah ketentuan undang-undang khususnya berkaitan dengan pidana mati, dan lembaga peradilan belum sepenuhnya melaksanakan ketentuan undang-undang yang memuat ancaman berupa pidana mati dan proses eksekusi terhadap terpidana mati masih menimbulkan diskriminasi dan masalah, sehingga hal tersebut menimbulkan masalah dan ketidakpastian hukum.Penelitian menunjukkan bahwa, perspektif Mahkamah Konstitusi terhadap pidana mati berprinsip bahwa pidana mati tidak bertentangan dengan Undang-Undang Dasar Negara RI Tahun 1945. Sedangkan Mahkamah Agung dalam beberapa putusannya memutuskan terlihat tidak konsisten. Penerapan ketentuan peraturan perundang-undangan yang memuat ancaman pidana mati bagi setiap pelaku tindak pidana masih terdapat diskriminasi, terutama penjatuhan pidana mati masih terbatas pada pembunuhan berencana dan tindak pidana terorisme. Proses pelaksanaan eksekusi terhadap terpidana mati masih terdapat permasalahan, yaitu adanya diskriminasi, baik jangka waktu maupun pelaksanaan eksekusi terhadap terpidana mati. Mahkamah Konstistusi dan Mahkamah Agung sebagai lembaga peradilan maupun lembaga negara terkait lainnya, disarankan dalam setiap putusan dan dalam perubahan KUHP kedepan, berkaitan dengan pidana mati hendaknya dipertahankan dan bersikap konsisten. Terhadap tindak pidana yang diancam dengan pidana mati dan tindak pidana tertentu lainnya lembaga peradilan disarankan untuk melaksanakan sepenuhnya dan bersikap objektif. Serta proses pelaksanaan eksekusi, baik jangka waktu maupun hak-hak terpidana mati hendaknya dirumuskan aturan konkrit dan dikontruksikan dalam putusan hakim, sehingga adanya kepastian hukum terhadap proses eksekusi dan hak-hak dari terpidana mati. Kata kunci : pidana mati, peradilan, Indonesia.